Perceptions of seriousness regarding symptoms of periodontal disease in adolescents age 18 years old - Vijani, Rizky; Susilawati, Sri; Setiawan, Asty Samiaty (Universitas Padjadjaran, 2013)
Introduction: Perception is the process of object observations about something using the five senses. Everyone has a different perception of the same object, although in this case are the symptoms of periodontal disease. The purpose of this study is to determine the self-perception of the seriousness of the symptoms of periodontal disease in adolescents aged 18 years SMAN 8 Bandung. Methods: This study was a descriptive study with a survey method. The methods used in sampling is a method of random sampling technique. Sample studied was 18-year-old teenager in Senior High School 8 Bandung students. as much as 148 student. Results: The results shows that respondents' perception of the seriousness of the symptoms of periodontal disease to get 555.8.average point. Conclusion: Based on the research result, it can be conclude that on 18-year-old student at SMAN 8 Bandung gained a serious perception of the symptoms of periodontal disease.